Journal of a trip to North America
Illustrated journal (87 pages; 1894 June 4-July 26) kept by an unknown German student sailing from Bremen, Germany, on a visit to New York, N.Y., Chicago, Ill., and other places in North America.
Facsimile.
Collection material in German.
Forms part of: Miscellaneous Manuscripts collection.
Formerly cataloged under the heading Schönhals (?), a place name mentioned in the journal.
Keywords: Bremen (Germany) -- Description and travel; Chicago (Ill.) -- Description and travel; New York (N.Y.) -- Description and travel; North America -- Description and travel